Study on the Properties of Vertical Carbon Nanotube Films Grown on Stainless Steel Bipolar Plates - Congda Lu (Materials, 2019)
Research on the conductivity and corrosion resistance of stainless steel bipolar plates in a proton exchange membrane fuel cell (PEMFC) is commonly performed in a normal-temperature environment (about 20 °C). However, these fuel cells must function in low-temperature environments (lower than 0 °C) in some conditions, such as in vehicle fuel cells and in portable power supplies that operate during the winter in northern China. Stainless steel bipolar plates have higher requirements in terms of their hydrophobic and anti-icing properties, in addition to needing high conductivity and corrosion resistance. In this study, carbon nanotubes (CNTs) are grown on the surface of 304 stainless steel (304 SS) without a catalyst coating by plasma-enhanced chemical vapor deposition (PECVD), which is a simple and cheap method that allows stainless steel to be used as bipolar plates in low-temperature environments. The Raman spectroscopy and scanning electron microscopy (SEM) results show that the CNTs grown on the surface of 304 SS have different morphologies. The stainless steel samples with different CNT morphologies are tested by hydrophobicity and in situ icing experiments to prove that vertical CNTs can achieve a superhydrophobic state and have good anti-icing properties. The interfacial contact resistance (ICR) of the bare 304 SS and the 304 SS with vertical CNTs is compared by voltammetry, and then the corrosion resistances of both types is compared in a simulated PEMFC environment via a three-electrode system. Consequently, the ICR of the 304 SS with vertical CNTs was lower than the bare 304 SS. The corrosion potential was positive, and the corrosion current density was greatly reduced for the stainless steel with vertical CNTs grown directly on its surface when compared with the bare 304 SS. The experimental results show that vertical CNTs have good application prospects as bipolar plates for PEMFCs in low-temperature environments.